Idiopathic pseudoaneurysm of the popliteal artery with endovascular treatment: A case report - Martin Rief, MD PhD; Angelika Rief, MD; Helmar Bornemann-Cimenti, MD PhD; Peter Rief, MD PhD (Radiology Case Reports, 2023)
Popliteal pseudoaneurysms are a rare vascular pathology, usually caused by trauma or iatrogenic interventions. Idiopathic cases are exceptionally uncommon. This case report aims to describe the diagnosis and successful endovascular treatment of an idiopathic pseudoaneurysm of the popliteal artery in a 90-year-old bedridden female patient presented with acute pain and swelling in the left knee at the emergency department. The patient underwent successful endovascular treatment with a covered stent and thrombin injection, leading to complete exclusion of the pseudoaneurysm. Popliteal pseudoaneurysms are a rare pathology, and idiopathic cases are even more uncommon. Endovascular therapy for popliteal pseudoaneurysms is associated with lower morbidity and mortality rates compared to open surgical repair. This case report highlights the importance of interdisciplinary collaboration between vascular surgeons and interventional radiologists in the management of rare vascular pathologies.